Efektivitas Program Indonesia Pintar dalam Mengurangi Angka Putus Sekolah - Dina Januarti; Tazkiah Fitriatul Imandah (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
The high dropout rate in Indonesia, particularly among lower-middle-income households, is a problem that requires serious attention. Data from the Central Statistics Agency (BPS, 2023) show that the dropout rate increases with each level of education, with the poorest households facing a risk two to three times higher than the wealthiest households. The Indonesia Pintar (PIP) program was launched as a government initiative to ensure the continuity of education for students from low-income families. This study aims to analyze the effectiveness of PIP in reducing dropout rates, identify supporting and hindering factors in its implementation, and formulate evidence-based policy recommendations. This study employs a descriptive qualitative method using a Systematic Literature Review (SLR) approach through thematic synthesis of 15 selected scientific articles retrieved from Google Scholar and Sinta, with the criterion of publication years 2021–2026. The findings indicate that the PIP program positively contributes to alleviating the burden of education costs and reducing dropout rates, particularly among students from lower-middle-income families. However, its implementation remains hindered by inaccuracies in beneficiary targeting, delays in fund disbursement, insufficient outreach, and weak oversight of aid usage. This study concludes that the effectiveness of the PIP needs to be improved through cross-agency data synchronization, strengthening program outreach, and developing clear standard operating procedures (SOPs) so that the program can be more targeted and have a more significant impact on equitable access to education in Indonesia.